ALAT PENDETEKSI KEBAKARAN MENGGUNAKAN NODEMCU ESP8266 WATERPUMP FLAME SENSOR DAN SENSOR MQ-2 BERBASIS WEB - Subhan, Sauqi; Subandi, Subandi; Imelda, Imelda; Yudha Sakti, Dolly Virgian Shaka (Universitas Budi Luhur, 2023)
Fires are often caused by human carelessness due to various factors such as, leaks from LPG gas cylinders, electrical short circuits, cigarette butts that are discarded carelessly can cause fires that can cause fires and can spread to flammable items. Fires can cause material loss and damage to many people affected by fire disasters and can even cause bodily injury and take lives. The method used for this research is the prototype method, the prototype method is a system development technique that makes the developer's work easier because the client knows a clear picture of the system that will be made by the developer. The purpose of this research is to create a website-based fire detection tool to minimize material loss and damage for many people affected by fire disasters. This research is designed using a NodeMCU microcontroller used as a data processor and a link to the website to monitor the work of the flame sensor and MQ-2 sensor online. Flame sensor is used to detect fire and MQ-2 sensor is used to detect smoke, Buzzer is used to give alarm or sound if there is fire and smoke detected by MQ-2 sensor and flame sensor, DC Relay is used to turn on the waterpump if the relay from the sensor reaches the specified limit to turn on the waterpump, the waterpump will turn on as an early prevention of fire if the fire sensor and smoke sensor detect fire and smoke. The result of this research is that the system is able to provide accurate data through the website as a notification notification so that it can notify if a fire occurs